PRELIMINARY EVIDENCE OF GROWTH INFLUENCE ON CARBON STABLE ISOTOPE COMPOSITION OF Undaria Pinnatifida - de Carvalho, Matheus Carvalho; Hayashizaki, Ken-Ichi; Ogawa, Hisao; Kado, Ryusuke (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Cultured sporophytic thalli of Undaria pinnatifida were collected at different periods of the year from Okkirai Bay, northeastern Japan. 13C of the thalli collected in January was much higher than that of the thalli collected in March, and young thalli collected in March showed a tendency towards lower 13C values comparing with adult ones. U. pinnatifida thalli grew fast in January, while young thalli in March showed slow growth due to the light limitation caused by shading adult thalli. Therefore, the growth rate of thallus may relate to 13C. Ongoing studies aim to quantitatively describe this relation and to search similar results for other species.